The application of the numerical method of evaluating the efficiency of grinding wheels and coolants for grinding nickel chromium alloy to specification E.P.K.31 (Henry Wiggin Ltd.) also the evaluation of surface residual stresses induced into the material by grinding: progress report no. 2 - Purcell, J. (College of Aeronautics, 1963)
SUMMARY The material is presenting phenomena which though met and recognised previously the significance to the grinding process was on these previous occasions not critical. With this material, instead of a wheel life variation of 0.5% maximum there can be 3096 to 40% reduction in expected wheel life. A detailed explanation of this element of wheel face life will be included in the fine_ report when repeatable test results to substantiate the parley will be available. The test on soluble type coolants have not as yet been as successful as one would have hoped and it is intended to ask the supplier if an improvement can be made from the knowledge gained by the test here reported. The workpiece in all cases where soluble coolants were used remained cool, but with the very limited number of oil coolants some temperature rise in the workpiece is experienced. This temperature rise is not very critical if the workpiece is of sufficient surface area to allow cooling to take place more rapidly. The test piece used in the laboratory is 2.5 ins x 6 ins. long, and is now 0.5 ins. thick (originally 1.0 ins). The calculation is made and included for wheel specification Carborundum 5A 46/54 0.8 V.50 using Fletcher Miller Product M7/63 This is the first result which has given a performance life long enough to make these calculations and is included to enable any firm who must use results immediately to make use of our work. While not wishing to depreciate this product or to appear over enthusiastic I shall be surprised if improved life is not achieved but this fuller calculation will allow further appreciation of the numerical methods we are using.